Improvements in the management of rheumatic patients from vertebral image obtained through dual-energy X-ray absorptiometry - D. Gatti; L. Idolazzi; O. Viapiana; M. Rossini; C. Pompermaier; S. Adami (PAGEPress Publications, 2011)
The diagnosis of asymptomatic vertebral fracture is clinically useful and the identification of new fractures may influences the choice of appropriate therapeutic measures. In order to identify moderate and asymptomatic vertebral deformities in an objective and reproducible manner, vertebral morphometry is performed. This method measures the vertebral body's anterior, middle and posterior heights at the dorsal and lumbar level. Currently this technique is performed on lateral images of the spine obtained through the traditional X-ray method (radiological morphometry or morphometric X-ray radiography, MRX) and, more recently from images obtained through dual-energy X-ray absorptiometry (DXA) machines (visual assessment of x-ray absoptiometry scans or morphometric X-ray absorptiometry, MXA), commonly used to measure bone mineral density. The main advantage of MXA relative to MRX is the lower radiation dose to which the patient is exposed during the exam. In addition, MXA scans offers the advantage of acquiring a single image of thoracic and lumbar spine, without any distortion (e.g.: coning). The most obvious advantage of MXA is the opportunity of obtaining during the same session a bone mineral density evaluation, and digital images that are easily processable, manageable, recordable and comparable for the patient's follow up. A limitation of the MXA technique is the inferior quality of the images, that make often impossible the detection of the vertebral edges, and the impossibility to visualize the upper thoracic vertebral bodies. MXA, despite its intrinsic limitations, when carried out by trained personnel may provide substantial improvements in the management (diagnosis and follow-up) of rheumatic patients.